Survival of anterior cruciate ligament reconstruction in patients with Ehlers-Danlos syndrome: a comparison with anatomic risk factors in existing literature - Schmidt, Sebastian; Leite, Chilan Bou Ghosson; Bumberger, Alexander; Franco, Domenico; Jacobs, Cale Andrew; Richardson, Lars; Paschos, Nikolaos; Goertz, Simon; Berkson, Eric; Asnis, Peter; Lattermann, Christian (International orthopaedics, 2025)
Ehlers-Danlos Syndrome (EDS) is a connective tissue disorder characterized by joint hypermobility, ligamentous laxity, and frequent joint injuries. These features could increase the risk of anterior cruciate ligament (ACL) tears, typically managed through ACL reconstruction (ACLR). Surgical intervention in EDS is challenging due to potential complications such as poor wound healing and tissue fragility. Limited evidence exists regarding the outcomes of ACLR in EDS patients; therefore, in this study we aimed to evaluate survival rates of primary and revision ACLR and examine associated demographic and anatomic risk factors for failure after ACLR.